Intelligent handover for vehicular networks - Almeida, André Filipe Magalhães de (2014)
The increasing proliferation of mobile devices along with the evolution of access technologies has led to a growth on a variety of services which the end user has at his disposal. This technological development has resulted in a higher bandwidth availability at more competitive prices. Currently, the technological challenge involves integrating several services on different access technologies to ensure that the end user experience is ubiquitous, transparent and mobile. Regarding these goals, mobility is where the main problems are experienced, specially in services involving real-time traffic, which are not tolerant to long delays and are expected to work seamlessly. An approach to tackle this issue within the vehicular networks scenario is analyzed in this work. A new mobility solution is suggested, along with methodologies in order to provide users the ability to interact with real-time services, across different access technologies, without service disruption. The new proposal is based on Fast Handovers for Mobile IPv6 (FMIPv6) mobility protocol with 802.21 IEEE Media Independent Handover (MIH) services and supported by a new logical architecture of software for MIH Function (MIHF).